Clinical efficacy of ulinastatin in the treatment of unliquefied pyogenic liver abscess complicated by septic shock: A randomized controlled trial - Mingfeng Guo; Bing Zhou (Immunity, Inflammation and Disease)
Abstract Introduction This study determined the therapeutic effect of ulinastatin (UTI) on unliquefied pyogenic liver abscesses complicated by septic shock (UPLA‐SS). Methods This was a randomized controlled trial involving patients with UPLA‐SS who underwent treatment at our hospital between March 2018 and March 2022. The patients were randomly divided into control (n = 51) and study groups (n = 48). Both groups received routine treatment, but the study group received UTI (200,000 units q8h for >3 days). Differences in liver function, inflammatory indices, and effectiveness between the two groups were recorded. Results Following treatment, the white blood cell count, and lactate, C‐reactive protein, procalcitonin, tumor necrosis factor‐α, and interleukin‐6 levels were significantly decreased in all patients compared to the admission values (p < .05). The study group had a faster decline with respect to the above indices compared to the control group (p < .05). The study group length of intensive care unit stay, fever duration, and vasoactive drug maintenance time were all significantly shorter than the control group (p < .05). The total bilirubin, alanine aminotransferase, and aspartate aminotransferase levels were significantly lower in the study and control groups after treatment compared to before treatment (p < .05); however, the study group had a faster recovery of liver function than the control group (p < .05). The overall mortality rate was 14.14% (14/99); 10.41% of the study group patients died and 17.65% of the control group patients died, but there was no statistically significant difference between the two groups (p > .05). Conclusion UTI combined with conventional treatment significantly controlled the infection symptoms, improved organ function, and shortened the treatment time in patients with UPLA‐SS.